IMPLEMENTASI MANAJEMEN SUMBER DAYA TENAGA KEPENDIDIKAN DALAM MENINGKATKAN KUALITAS LAYANAN PENDIDIKAN AGAMA ISLAM DI MTs AL AZHAR CENTER BATURAJA SUMATERA SELATAN - Rizky Denni Fratama (UNISAN JURNAL, 2024)
This research aims to analyze the implementation of teacher resource management in improving the quality of Islamic education services for students at DI MTs Al Azhar Center Baturaja Sumatera Selatan , as well as the factors that influence the implementation and evaluation of the implementation. The research method used is descriptive research with a qualitative approach. Data were obtained through interviews, observation, and document study. The results of the research show that the implementation of teacher resource management is carried out through the management of professional teachers, the fulfillment of teacher needs, the improvement of teacher competence, and the development of work culture. The factors that influence the implementation include the support of the school principal, good communication between teachers, clear and consistent policies, and strict supervision. Evaluation of the implementation is carried out through measuring the performance of teachers and students, assessing training programs, and measuring student and parent satisfaction. The results of the evaluation show that the implementation of teacher resource management has successfully improved the quality of Islamic education services for students at DI MTs Al Azhar Center Baturaja Sumatera Selatan